Treatment Indications of Carbon Solution-Assisted Nd:YAG Laser According to Patient Satisfaction: A Retrospective Study - Hüray Hügül; Defne Özkoca; Murat Kirişçi; Zekayi Kutlubay (Mattioli1885, 2023)
Background: Carbon solution-assisted Nd:YAG lasers were previously used in enlarged pores; hair removal; acne and acne scars; and facial rejuvenation. Objective:The aim of this study is to determine the patient satisfaction for different treatment indications of carbon solution-assisted 1064 nm Nd:YAG lasers. Patients and Method: This is a retrospective study that included the patients who were treated with carbon solution-assisted 1064 nm Nd:YAG laser with any indication in a private dermatology practice. A pre-prepared carbon solution was applied 30 minutes before the laser treatment with the following parameters: a spot size of 8mm, fluence of 1.3 J/cm2 and a frequency of 8Hz. Patient satisfaction was assesed with GAIS. Results: A total of 272 patients were included; of these 70 patients had acne lesions, 135 patients had melasma, 27 patients had post-inflammatory hyperpigmentation, 17 patients had ephelides and 23 patients had solar lentigines. The mean patient satisfaction for solar lentigo patients (4.35/5) was greater than for that of acne patients (4.26/5) which was greater than that of ephelide patients (3.94/5) which was greater than that of melasma patients (3.67/5) which was greater than that of post inflammatory hyperpigmentation patients (2.30/5) Conclusion: This study revealed that carbon solution-assisted 1064 nm Nd:YAG laser therapy is effective in the treatment of solar lentigo, acne vulgaris, ephelides and melasma. However, it fails to provide therapeutic efficacy in post inlammatory hyperpigmentation.